A Critical Look at Innovation Profile and Its Relationship with Pharmaceutical Industry (International Journal of Scientific Research and Management (IJSRM), 2017)
Background: The pharmaceutical sector undertakes extensive research and development (R&D). Pharmaceutical industries have continued to launch an appreciable number of new medicines, different pharmaceutical formulations, new indications and other innovations that contribute to the growth of this sector. New novel medicines are increasingly essential for continued success given the number of standard medicines now available as low cost generics or biosimilars. Consequently, innovation is a fundamental element in pharmaceutical company competition. Not all innovations though are the same size, type or category with differentiation of innovation essential for commercial success. However, given the wide range of definitions used in the literature, the framing may diffuse. Currently, there are several types and categories of innovation are deficiently harmonized and poorly stratified resulting in analysis trends and provide major obstacles to innovation’s differentiation and in assessing the company’s innovative dominant characteristic in the sector. The objective of this study is to stratify and organize, didactically, the field of definitions and concepts of innovation and provide a structural and operational delineation, from a critical point of view, for the classifications of innovation applied to the pharmaceutical industry.